EXPERIMENTAL ELECTRO COAGULATION UNIT FOR PRETREATMENT OF MAINS WATER FOR STEAM GENERATION AT THERMAL POWER PLANTS - USMONOV NIZOMJON ORIFOVICH; ISAKHODJAYEV KHAYRULLA SUNNATULLAYEVICH; ALIMOVA LOLA ODILJONOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
The article covers the state of pre-chemical treatment of natural water at Tashtpp with the use of aluminum sulphate and the creation of an experimental unit for producing coagulant, aluminum sulphate, as well as a block diagram of the proposed electrocoagulation unit for pre-treatment and clarification of water. An electrocoagulation technology for pre-treatment and clarification of water for Tashtpp steam boilers has been developed.